Systematic review of the results of reverse shoulder arthroplasty on the quality of life of the elderly: a bioethical perspective (Research, Society and Development, 2022)
Background - Worldwide, the proportion of people aged 60 and over (seniors) is growing faster than any other age group. Reverse shoulder arthroplasty is a surgical intervention that reduces pain and improves functionality lost by the degenerative joint process that is frequent in the elderly. Objective: Quality of life (QOL) and the bioethical discussion about the importance of the elderly's QOL as a right to be guaranteed for aging with dignity, is it urgent for aging with dignity? Method: Systematic review of the relationship between reverse shoulder arthroplasty and QOL in the elderly through the analysis of results. LILACS, MEDLINE/PUBMED, and SCIELO databases were searched in December 2021, with titles, abstracts and keywords of original articles in English, Portuguese and Spanish published from January 2017 to December 2021 evaluated using the descriptors DeCS: shoulder arthroplasty, quality of life, elderly, outcome evaluation. Result: Nine articles from an initial sample of 21,459 remained at the end of the selection process. The majority (8) observed an improvement in QOL after reverse shoulder arthroplasty, in a follow-up of more than 12 months. Conclusion: Functionality was found as an essential component in the QOL of the elderly, and its improvement as an effect of reverse shoulder arthroplasty. It was observed that despite these descriptors being widely used individually, as shown by the raw data of the research, with 21,459 articles, their synchronized relationship has not been studied, having been found only eight articles that worked with them together.